Fast Heating-Assisted One-Pot Copper-Catalyzed Sulfonylation and Sulfochlorination of Styrenes - Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Almodovar-Fajardo, I (John Wiley and Sons Inc, 2022)
Here, a strategy for the synthesis under fast-heating conditions of vinyl sulfones and β-chlorosulfones from styrene derivatives, tosyl chloride (TsCl) as sulfonyl and chlorine source, and CuBr-neocuproine as the catalytic system is reported. The reaction occurs through an atom transfer radical addition (ATRA) mechanism to generate the sulfochlorinated adducts followed by E2 elimination to generate the vinyl sulfones. This methodology allows a wide range of vinyl sulfones and β-chlorosulfones to be obtained using inexpensive reagents in one and five minutes respectively. These reactions appear as an interesting fast and easy-to-handle alternative to obtain these compounds. © 2022 Wiley-VCH GmbH.